Structural Anisotropy in Stretchable Silicon. (2nd May 2019) - Curtis, Sabrina M.; Tompkins, Randy P.; Nichols, Barbara M.; Graziano, Milena B.; Kierzewski, Iain; Smith, Gabriel; Leite, Marina S.; Lazarus, Nathan
Abstract: Patterned planar silicon (Si) semiconductor structures able to conform around 3D surfaces are promising candidates for wearable devices from solar cells to displays. Despite the known anisotropic material properties of crystalline semiconductors, prior evaluations have assumed isotropic stretchable mechanical behavior. The effect of structural anisotropy on the mechanical stretching behavior of 100 single crystalline Si planes is demonstrated through models and experiments. 3D finite element analysis results show serpentines fabricated and strained loaded on the dense 111 family of planes will have maximum von Mises peak stresses that are 20% higher than those fabricated in the <100> direction on the 100 family of planes. A fabrication process is presented to release in‐plane Si serpentine test structures from (100) silicon‐on‐insulator wafers aligned parallel to the <110> and <100> crystallographic orientations. The released test structures can accommodate strains to 84%. Raman spectroscopy is used to characterize anisotropic effects on the internal stresses of Si serpentines. Raman measurements confirm two different maximum stress locations on <110> and <100> Si serpentines, resulting in two different break locations. All results show anisotropy plays a critical role in the mechanical behavior of stretchable Si serpentines and must be considered during design of stretchable semiconductor structures. Abstract : Structural anisotropy plays a critical role in determining the maximum stress and fracture location of Si‐based stretchable structures. Finite element analysis and experiments demonstrate that the maximum strain‐to‐rupture of in‐plane Si serpentines varies by 14–21%, depending on crystal plane and orientation. The best stretching performance is found for Si serpentines patterned parallel to the <100> direction on 100 Si planes.